Developing simulation games to advance public health nursing competence in baccalaureate education. Issue 2 (5th January 2023) - Schofield, Ruth; Chircop, Andrea; Currie, Genevieve; Foster, Sue; Hamilton, Julie; Kall, Denise; Luctkar‐Flude, Marian; Riselli, Dawn Mercer; Oke, Stacy; Ryan, Maureen M.; Sanders, Tanya; Tam, Susan; et al.
Abstract: We describe the development of an innovative baccalaureate nursing education strategy for public health nursing. Virtual simulation pedagogy is known to be effective for acute care nursing practice while less known for public health nursing. Three Canadian nursing schools, the Canadian Association of Schools of Nursing (CASN), and the Canadian Alliance of Nurse Educators using Simulation (CAN‐Sim) partnered to develop three public health nursing virtual simulation games. Learners work through unfolding population health scenarios, simulating public health nursing practice focused on entry level public health nursing competencies. Each game fosters clinical reasoning and collaborative, community decision‐making to respond to population health issues during community assessment, evidence‐informed health promotion planning, and evaluation processes. A companion guide was developed to support best practices in implementing virtual simulation and promote optimum student learning using the public health nursing games.